(3VeGfGJ GdeJge aj eQMdI GdJMbjb GdEHJOGFj (B/ s - (3YHO GdYXje NGdO UGdM GdZWGSs; (3MSfjf YHjOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2013)
(3ehVhY VeGfGJ GdeJge ai eQMdI GdJMbjb GdGHJOGFi gh ef GdehVhYGJ GdegeI GdJi JYfi HMbhb GdEfSGf h VeGf MQjGJg h dbO dGbi eKd gPG GdehVhY QhGLG cKjQG ai cJH Gdabg h Pdc dMLe GdGaJFGJ GdMGUd Ydi MQjI GdCaQGO SjeG GdeJge GdPi GdMdbI GdCVYa ai SdSdI GdELQGAGJ GdLfGFjI(B. (3fYe ef Mb GdOhdI eeKdI ai eDSSGJgG JYbH GdLfGI h eYbGHJge (B. (3h dcf Pdc dGHO Cf jJe ai WGHY ef GdTQYjI GdELQGFjI Pdc Cf Mbhb GdEfSGf gi GdeUdMI GdCSei GdCLOQ HGdMeGjI h GdChdi HGdQYGdjI h NjQ GdYOGdI Cf jadJ eJge ef GdYbGH ef Cf jXde HQF hGMO XdeG h YOhGfGs
(3CWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj (B2013.s
(3HHdjhLQGajG(B: (3UaMGJ (B378-393.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdJMbjb GdGHJOGFjs; (3SQjI GdJMbjbs; (3LgGJ GdJMbjb GdGHJOGFj (B((3GdCUdjI , GdHOjdI , GdGSJKfGFjI(B)s; (3GdJUQa aj GdJMbjb s; (3GdJfbjH Yf GdGOdIs; (3GdJMbjbGJ GdbhdjIs; (3GdGLQGAGJ GdGMJjGWjIs; (3GdMHS GdGMJjGWjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs